ACCOUNTING CHALLENGES IN (VAT) APPLICATION (AN ANALYTICAL STUDY IN THE GENERAL AUTHORITY FOR TAXES/DHI QAR GOVERNORATE) - Mahdi Saleh Jaber; Ali Fakhir Kadhim Alwajid (Journal of Economic and Economic Policy, 2026)
Objective: This paper examines the issues the accounting issues surrounding the use of Value Added Tax (VAT) in Iraq were discussed. The law and regulations surrounding this tax were reviewed and the accounting practice applied in computing it reviewed. Method: The research was based on gathering the data by reviewing the literature on the topic, interviewing the officials of the related government agencies, and survey of the sample of commercial establishments. Results: The findings of the research indicated that there were numerous challenges the accounting challenges in the application of Value Added Tax (VAT) in Iraq are: ambiguity in the laws and procedures, problems with calculation of the tax, preparing tax returns, low awareness and training among staff and inadequate requisite technological facilities. Novelty:The research paper has ended by providing a combination of suggestions that will enhance accounting and administrative standards in the implementation of the value-added tax, such as streamlining operations, improving training and awareness, and provision of supportive technical systems.